Discriminant Analysis of Undaria pinnatifida Production Areas Using Trace Elemental Analysis - Mikio Kaihara (International Journal of Analytical Chemistry)
Increasingly, attention is being paid to declaring the origin of agricultural and marine products after the advent of the bovine spongiform encephalopathy (BSE; commonly known as mad-cow disease). The display of the production centers on U. pinnatifida has been required in Japan since 2006. As an example of testing in another marine product, near-infrared spectra (NIR) and trace elemental analysis of U. pinnatifida are proven effective methods for discriminating production centers by us and Food and Agricultural Materials Inspection Center (FAMIC). In the present study, we found that X-ray fluorescence analysis of Br was also effective for the discrimination of production centers. The results of our study suggest that a combination of NIR and X-ray fluorescence analysis is a convenient and efficient method for determination due simple sampling procedures and increased effectiveness.